OS LIMITES DA ATUAÇÃO DA ADVOCACIA-GERAL DA UNIÃO NA POLÍTICA ESTATAL DE “DESJUDICIALIZAÇÃO”: THE ATTORNEY GENERAL’S OFFICE´S PERFORMANCE LIMITS IN THE STATE POLICY ON “DEJUDICIALIZATION” (Revista Direito em Debate, 2021)
In this article, we analyzed the main obstacles and alternatives for the participation of Federal Government's, through the Attorney General's Office (AGU), in the policy of alternative dispute resolution (ADR), which was adopted by the Code of Civil Procedure in 2015. The analysis was carried out from the perspective of the postulate of dejudicialization and considers the scenario of the litigation crisis within the Brazilian Judiciary. The descriptive methodology was used, pointing out some of the main problems and gains of the use of alternative dispute resolution management, concluding that, although Brazil has adopted the referred policy of dejudicialization it was not accompanied by the proper structuring and instrumentalization of a considerable number of institutions legitimized to carry it out so that they could exercise it fully and effectively. As a result, the difficulties encountered by the AGU, illustrated in this paper, but which afflict a considerable part of the State representatives are verified, which legitimizes the study and challenges the law operator to seek systematic solutions to this problem.
Keywords: Alternative dispute resolution; Union Attorney General; Legislation; Dejudicialization; Peaceful settlement of disputes